Broadband, High‐Speed, and Large‐Amplitude Dynamic Optical Switching with Yttrium‐Doped Cadmium Oxide. (13th December 2019) - Saha, Soham; Diroll, Benjamin T.; Shank, Joshua; Kudyshev, Zhaxylyk; Dutta, Aveek; Chowdhury, Sarah Nahar; Luk, Ting Shan; Campione, Salvatore; Schaller, Richard D.; Shalaev, Vladimir M.; Boltasseva, Alexandra; Wood, Michael G.
Abstract: Transparent conducting oxides, such as doped indium oxide, zinc oxide, and cadmium oxide (CdO), have recently attracted attention as tailorable materials for applications in nanophotonic and plasmonic devices such as low‐loss modulators and all‐optical switches due to their tunable optical properties, fast optical response, and low losses. In this work, optically induced extraordinarily large reflection changes (up to 135%) are demonstrated in bulk CdO films in the mid‐infrared wavelength range close to the epsilon near zero (ENZ) point. To develop a better understanding of how doping level affects the static and dynamic optical properties of CdO, the evolution of the optical properties with yttrium (Y) doping is investigated. An increase in the metallicity and a blueshift of the ENZ point with increasing Y‐concentrations is observed. Broadband all‐optical switching from near‐infrared to mid‐infrared wavelengths is demonstrated. The major photoexcited carrier relaxation mechanisms in CdO are identified and it is shown that the relaxation times can be significantly reduced by increasing the dopant concentration in the film. This work could pave the way to practical dynamic and passive optical and plasmonic devices with doped CdO spanning wavelengths from the ultraviolet to the mid‐infrared region. Abstract : Yttrium‐doped cadmium oxide films grown on fused silica exhibit Fabry–Perot resonance. Interband‐pumping shifts the resonance, leading to broadband transmission/reflection modulation. Up to 135% reflection‐modulation is demonstrated in the mid‐infrared region, with picosecond response times. The relaxation times and the epsilon‐near‐zero wavelengths can be tailored by controlling the doping level. This has applications in tunable optical/plasmonic devices spanning the ultraviolet to the mid‐infrared region.